2023
DOI: 10.7150/thno.86007
|View full text |Cite
|
Sign up to set email alerts
|

Dual targeting PET tracer [68Ga]Ga-FAPI-RGD in patients with lung neoplasms: a pilot exploratory study

Abstract: Rationale: Early discovery, accurate diagnosis, and staging of lung cancer is essential for patients to receive appropriate treatment. PET/CT has become increasingly recognized as a valuable imaging modality for these patients, but there remains room for improvement in PET tracers. We aimed to evaluate the feasibility of using [ 68 Ga]Ga-FAPI-RGD, a dual-targeting heterodimeric PET tracer that recognizes both fibroblast activation protein (FAP) and integrin α v … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…A clinical study carried out on 22 patients and recently published by Zhao et al demonstrated an improved lesion detection rate and metastatic delineation of 68 Ga-FAPI-RGD in comparison to 18 F-FDG [193]. Similar observations were reported in a pilot exploratory study on patients (n = 51) with suspected lung cancers [194]. With the stated advantages, the FAPI-RGD should be further explored for therapeutic applications.…”
Section: Other Developments Of Dual-targeting Moleculessupporting
confidence: 69%
“…A clinical study carried out on 22 patients and recently published by Zhao et al demonstrated an improved lesion detection rate and metastatic delineation of 68 Ga-FAPI-RGD in comparison to 18 F-FDG [193]. Similar observations were reported in a pilot exploratory study on patients (n = 51) with suspected lung cancers [194]. With the stated advantages, the FAPI-RGD should be further explored for therapeutic applications.…”
Section: Other Developments Of Dual-targeting Moleculessupporting
confidence: 69%
“…In a recent investigation, Wang et al [ 89 ] performed a pilot cohort study to assess the viability of [ 68 Ga]Ga-FAPi-RGD, a bifunctional PET tracer targeting both fibroblast-activating protein (FAP) and α v β 3 integrin, in identifying lung cancers. This tracer was evaluated alongside [ 18 F]F-FDG and the single-function tracers [ 68 Ga]Ga-RGD and [ 68 Ga]Ga-FAPi for lung cancer detection efficacy.…”
Section: Drug Delivery Systems and Recognition In Angiogenesis And Lu...mentioning
confidence: 99%
“…Additionally, it achieved superior precision in evaluating mediastinal lymph nodes (99.7% vs. 90.9%, p < 0.001) and detected more metastatic sites (254 vs. 220). A notable distinction was also observed in the uptake of primary lesions between [ 68 Ga]Ga-FAPi-RGD and [ 68 Ga]Ga-RGD (SUVmax, 5.8 ± 4.4 vs. 2.3 ± 1.3, p < 0.001) [ 89 ]. Radiolabeled fibroblast-activating protein (FAPI) inhibitors are significant markers for the non-invasive imaging of tumor microenvironments.…”
Section: Drug Delivery Systems and Recognition In Angiogenesis And Lu...mentioning
confidence: 99%
“…A similar extensive study with radiolabeled FAPI multimers is warranted to arrive at a definitive conclusion. To enhance tumor uptake and retention, bi-specific heterodimeric radiotracers such as those targeting both FAPI and integrin α v β 3 (FAPI-RGD) have also been developed [20][21][22]. Such radiopharmaceuticals can overcome the compromised sensitivity and specificity, attributable to tumor heterogeneity and complexity of the mono-targeting radiotracers for potential therapeutic applications.…”
Section: Fapi-46-lbu Fapi-46-ebmentioning
confidence: 99%